Study on the Mechanism of Sparks Generated Mechanical Friction - He Pan; Yang Zhang (Journal of Engineering)
In the field of explosion protection, measures must be taken to prevent ignition sources due to mechanical friction and impact. One of the most dangerous sources of ignition in methane-air mixtures is sparks, which are easily induced by friction and impact from light metals. In general, sparks and hot surfaces are coexistent in the friction processes of metal contacts. The questions are whether sparks are a truly effective ignition source and whether the nature of materials plays a decisive role in the ignition ability of sparks. Therefore, this research focuses on the temperature of hot surfaces and sparks generated by friction between pure copper, Q235A steel, and TC4 titanium alloy and the grinding wheel. The effect of the relative rotating speed on the friction temperature and friction spark characteristics is investigated. The result indicates that friction sparks are indeed easier to detonate gas than hot surfaces. Moreover, a mathematical model based on the heat transfer theory is used to prove that the sparks induced by friction from TC4 alloys are more hazardous than those induced by friction from copper and Q235A steel. The factors affecting the energy released by sparks are listed in the formula.